The Double Burden of Malnutrition among Adolescents from Zimbabwe: A Cross-Sectional Study - Ashleigh Pencil; Tonderayi Mathew Matsungo; Thomas Mavhu Chuchu; Nobuko Hongu; Naomi Hayami (Obesities, 2024)
(1) Background: The double burden of malnutrition (DBM) is an emerging public health concern among children and adolescents in developing countries. This study investigated the prevalence and factors associated with being underweight and overweight among adolescents. (2) Methods: This cross-sectional study was conducted among 423 adolescents across 10 high schools in Harare. A questionnaire was used to collect data and weight for height-z-scores were used to compute body mass index. Pearson’s Chi-Square and multinomial logistic regression were used to test for associations and explore factors associated with being underweight or overweight at (p < 0.05). (3) Results: The median and IQR range for the participants was 16 (14–19) years. There were more girls 53.2%, than boys 46.8% (p = 0.002), and more 14–16-year-olds 54.1%, than 17–19-year-olds (p = 0.070). More boys 10% than girls 9.1% were underweight, whereas more girls 21.8% than boys 9.3% were overweight and obese (p = 0.002). By age, more 14–16-year -olds were underweight 12.7% than 17–19-year-olds 5.9%, whereas more 17–19-year-olds 16.2% were overweight than 14–16-year-olds (p = 0.070). Significant factors associated with being underweight were inadequate balanced nutrition knowledge [OR = 1.49 (0.139–0.997), p = 0.049], being in the 14–16 years age group [OR = 2.56 (1.137–5.779), p = 0.023], having formally employed [OR = 2.34 (1.008–5.428), p = 0.048] and unemployed [OR = 5.17 (1.263–21.116), p = 0.022] household heads. Significant factors associated with overweight were being a girl [OR = 0.32 (0.168–2.561), p < 0.001, and having formally employed household heads [OR = 2.00 (1.044–1.206), p = 0.037]. The employment status of the household head (being formally employed) was the only factor which associated with both underweight and overweight statuses. (4) Conclusions: Although underweight and overweight statuses co-exist, among adolescents, those who are overweight appear to be more than those who are underweight. Significant factors associated with being underweight were inadequate nutrition knowledge, being 14–16 years old, and having formally employed or unemployed parents. While being a girl and having formally employed parents were significant determinants of the overweight status. This paper calls for more awareness of DBM and context-specific interventions targeting obesity in a country where undernutrition has been traditionally prioritized at policy and program levels.